(3hKjbI Hjf GdYdeGA hGdMGL CMeO HGj aj hdGjJg hQaY GdeXGde Yf GdQYjIs
(3ChdgG (B:s
(3gPG XgjQ cQje, hNWGH hGVM CeQ eHGQc Yeje, hEYdGe UGdM YXje s
(3BNQgG (B:s
(3aMSH GdhGba Ydjg Gdhbha YfOg hYOe GdeNGdaI hcJH HEPf GdSGOGJ hGdCejQ ceG PcQ HJGQjN ChGNQ LeGOi GdChdi SfI (B1246 (3g` s
(3Vef eLehY , JQJjHgG (B: (3ef U (B194 - (3U(B197s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B468 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(709 (3O(B) s
Keywords: (3GdJGQjNs